The Effect of Independence, Professionalism, Competency and Auditor’s Experience on the Quality of Audit Report (Empirical Study at BPK Perwakilan Provinsi Sulawesi Utara) - Jullie J. Sondakh2; Melina Yosephine Sihombing (Accounting and Finance Studies, 2023)
This study aims to determine the effect of independence, professionalism, competency and auditor’s experience on the quality of audit report. This study using a survey with census method using questionnaires distributed to all auditors in BPK Perwakilan Provinsi Sulawesi Utara. There were 138 questionnaires distributed around June until July 2023, but only 125 questionnaires returned so that response rate was 90,58%. The research model used is the multiple linear regression. The results show that professionalism, competency and auditor’s experience have a positive and significant effect on the quality of audit report, while independence has no significant effect. The implication of these findings show that the increase of professionalism, competency and auditor’s experience improve the quality of audit report. Coefficient of determination shows that independence, professionalism, competency and auditor’s experience simultaneously influence the dependent variable (the quality of audit report) by 68,50%, while the remaining 31,5% is influenced by other factors.